POLITENESS IN THE DAILY CONVERSATION OF UNAKI BOARDERS - Tri Fena Retty Yulianan Gultom; Didit Kurniadi (Jurnal CULTURE (Culture, Language, and Literature Review), 2017)
Nowadays, many people do not notice their sentences when they talk to others whether it is polite or not. Sometime, people use harsh word when they ask help to others. Even in conveying their purpose, they often use impolite sentence. They do not also regard their background, like status of their position, their social distance and the level of their needs. The polite words are usually conveyed by someone when the level of his or her need is high. But, the distance and position status are also the factor that determine someone to use polite or impolite sentence in the daily conversation, especially in conveying her or his need. Someone who does not have a close relationship, he or she will affect the sentences which are used. The sentences which are used will sound more polite than the sentences that used by them who have a close relationship. Because the closer someone’s relationship is, the harsher the sentences which are used. Even sometimes it sounds rude of and impolite. Someone’s position also affects the sentences which are used in speaking. The higher of the position is, the more polite of the sentences which are used. Otherwise, the lower of someone’s position or in the same position, the less polite the sentences which are used. According to this facts, the writer analyzes the difference of polite or impolite sentence in the daily conversation.The data which are used are primary data and secondary data. The methods which are used in getting the data are “metode simak, metode sadap, teknik simak bebas libat cakap, teknik rekam, and teknik catat”. In analyzing the data, the writer uses “metode agih”. Whilemethod of data presentation which is used by the writer is descriptive study with informal method.From the result of the research, it can be concluded that someone’s social distance and position really affects the sentences used and polite sentence in the daily conversation. A close social distance will make the sentences which are used sound less polite and rude. But, when the social distance is not close, it will make the  sentences used sound polite and good. So in the position status, the higher of the position is, the more polite sentences used.Keywords: Politeness, Daily Convdersation, Social Distance, Close Relationship,Descriptive Study